Management of Ruptured Intracranial Aneurysm with Deep Vein Thrombosis - Pandit, Sneha; Dube, Surya K.; Sokhal, Suman; Chaturvedi, Arvind (Journal of Neuroanaesthesiology and Critical Care, 2024)
Deep vein thrombosis (DVT) is a known complication of aneurysmal subarachnoid hemorrhage (aSAH), and anticoagulant therapy is crucial for its management. However, in case of a ruptured intracranial aneurysm in a patient of DVT, anticoagulant administration may lead to rebleeding. Anticoagulants are also associated with a risk of hematoma expansion. A systematic approach is required to weigh the risk and benefit ratio while managing such cases. We report the successful management of a 61-year-old female presenting with aSAH and associated DVT who had an intracranial vessel injury during intraoperative clipping of an aneurysm.
Keywords: anticoagulation; subarachnoid hemorrhage; deep vein thrombosis